Finite-element simulations of the influence of pore wall adsorption on cyclic voltammetry of ion transfer across a liquid–liquid interface formed at a micropore - Ellis, J.; Strutwolf, J.; Arrigan, Damien (Royal Society of Chemistry, 2012)
Adsorption onto the walls of micropores was explored by computational simulations involving cyclic voltammetry of ion transfer across an interface between aqueous and organic phases located at the micropore. Micro-interfaces between two immiscible electrolyte solutions (micro-ITIES) have been of particular research interest in recent years and show promise for biosensor and biomedical applications. The simulation model combines diffusion to and within the micropore, Butler–Volmer kinetics for ion transfer at the liquid–liquid interface, and Langmuir-style adsorption on the pore wall. Effects due to pore radius, adsorption and desorption rates, surface adsorption site density, and scan rates were examined. It was found that the magnitude of the reverse peak current decreased due to adsorption of the transferring ion on the pore wall; this decrease was more marked as the scan rate was increased. There was also a shift in the half-wave potential to lower values following adsorption, consistent with a wall adsorption process which provides a further driving force to transfer ions across the ITIES. Of particular interest was the disappearance of the reverse peak from the cyclic voltammogram at higher scan rates, compared to the increase in the reverse peak size in the absence of wall adsorption. This occurred for scan rates of 50 mV/s and above and may be useful in biosensor applications using micropore-based ITIES.